1967
DOI: 10.1016/0024-3205(67)90080-x
|View full text |Cite
|
Sign up to set email alerts
|

The cardiac -adrenergic receptor blocking actions of propranolol and its stereoisomers

Abstract: THE introduction o£ the beta-adrensrgic receptor blocking ageaC, dichloroisoproterenol (DCI), by Powell and Slater l provided the coat coapelling evidence in support of the dwl adrensrgic receptor hypothesis of Ahlquist 2 .Numerous other beta -receptor antagonists have since been introduced, including pronethalol 3 and propranolol 4' S . The competitive equilibrium nature of the adrenargic blockade produced by these agents suggests that that while they probablq possess affinity for the bate-adrenergic receptor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
11
0

Year Published

1968
1968
1989
1989

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 5 publications
6
11
0
Order By: Relevance
“…It seems that Y13-2, like propranolol, exhibits no cardioselectivity which has been claimed in the studies on practolol (13)(14)(15) YB-2 and its optical isomers in the doses required to inhibit the positive inotropic and chronotropic responses to isoproterenol and cardiac sympathetic nerve stimulations failed to alter the inotropic response to calcium chloride. The finding appears to be simi lar to the result obtained from the study on isoproterenol-antagonism of propranolol and its optical isomers (18).…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…It seems that Y13-2, like propranolol, exhibits no cardioselectivity which has been claimed in the studies on practolol (13)(14)(15) YB-2 and its optical isomers in the doses required to inhibit the positive inotropic and chronotropic responses to isoproterenol and cardiac sympathetic nerve stimulations failed to alter the inotropic response to calcium chloride. The finding appears to be simi lar to the result obtained from the study on isoproterenol-antagonism of propranolol and its optical isomers (18).…”
Section: Discussionsupporting
confidence: 80%
“…Whitsitt and Lucchesi observed no significant difference in the doses of propranolol required to antagonize the pharmacological and neurogenic beta-adrenergic stimulations in both isolated rabbit atria and anesthetized dogs (18). In the present study, a similar tendency was observed not only in the doses of propranolol but in those of YB-2 and its optical isomers in both isolated guinea pig atria and anesthetized dogs.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Howe and Shanks (19) reported that racemic propranolol and its optical isomers were equally effective in abolishing ouabain-induced arrhythmia, while the ]-isomer was a little more effective. Lucchesi et al (20), and Whitsitt and Lucchesi (21) found that both i and d-isomer of either propranolol or pronethalol were capable of suppressing ectopic ventricular automaticity induced by ouabain, and such suggests that there is no special relation between fl-blocking action and prevention of ouabain-induced arrhythmia. Somani and others demonstrated that local anesthetic action was essential for antiarrhythmic activity of j3-blocking agents (22,23 Tse and Han also found that ouabain enhanced the action of catecholamine on the auto maticity of Purkinje fibers causing ventricular arrhythmia (32).…”
Section: Discussionmentioning
confidence: 99%